Standing Waves and Acoustic Heating (or Cooling) in Resonators Filled with Chemically Reacting Gas - Anna PERELOMOVA; Weronika PELC-GARSKA (Archives of Acoustics)
Standing waves and acoustic heating in a one-dimensional resonator filled with a chemically reacting gas, is a subject of investigation. The chemical reaction of $A → B$ type, which takes place in a gas, may be reversible or not. Governing equations for the sound and entropy mode which is generated in the field of sound are derived by use of a special mathematical method. Under some conditions, sound waves propagating in opposite directions do not interact. The character of nonlinear dynamics of the sound and relative acoustic heating or cooling depends on reversibility of a chemical reaction. Some examples of acoustic heating in a resonator are illustrated and discussed.